2022
DOI: 10.1145/3546195
|View full text |Cite
|
Sign up to set email alerts
|

Author Reflections on Creating Accessible Academic Papers

Abstract: Academic papers demonstrate inaccessibility despite accessible writing resources made available by SIGACCESS and others. The move from accessibility guidance to accessibility implementation is challenging for authors. Our work focuses on understanding what challenges authors of academic papers face in creating content elements (e.g., tables, charts, images) to better understand how to improve accessibility. We classified 3866 content elements from 330 papers covering a 10-year sample of academic work from ASSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Interestingly, we observed that multiple data types were often used in conjunction, especially temporal data, which rarely appeared in isolation. Three papers, all of which aimed at devising frameworks, did not focus on presenting a specific data type, were classified as non-specific, underscoring the versatility and broad applicability of these frameworks for various data types (e.g., [30], [43], [56]).…”
Section: B Research Methodology 1) Study Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, we observed that multiple data types were often used in conjunction, especially temporal data, which rarely appeared in isolation. Three papers, all of which aimed at devising frameworks, did not focus on presenting a specific data type, were classified as non-specific, underscoring the versatility and broad applicability of these frameworks for various data types (e.g., [30], [43], [56]).…”
Section: B Research Methodology 1) Study Methodsmentioning
confidence: 99%
“…Research efforts in this domain serve various objectives. Some studies aim to develop guidelines for making educational materials more accessible (e.g., [43], [65]). In contrast, others employ data visualization dashboards to understand better the behavior of students with learning disabilities (e.g., [66]).…”
Section: B Research Methodology 1) Study Methodsmentioning
confidence: 99%
See 2 more Smart Citations